2006
DOI: 10.1016/j.bbrc.2005.11.119
|View full text |Cite
|
Sign up to set email alerts
|

Activation of connective tissue growth factor gene by the c-Maf and Lc-Maf transcription factors

Abstract: The Maf family of transcription factors is expressed during development of various organs and tissues, and is involved in a variety of developmental and cellular differentiation processes. We previously found that c-maf and mafB are strongly expressed in hypertrophic chondrocytes during cartilage development. Connective tissue growth factor (CTGF) is also expressed in hypertrophic chondrocytes. Adenovirus mediated introduction of c-maf gene into the mouse fibroblast cell line C3H10T1/2 strongly induced CTGF ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…To the best of our knowledge, the effect of an adenoviral Smad3 vector on CTGF protein levels in vivo has not yet been reported in the context of wound healing. Moreover, there is increasing evidence that CTGF is regulated to a significant extent by other intermediates, such as the transcriptional factors c‐Maf and Lc‐Maf independent of the canonical Smad‐dependent TGF‐β pathway 32 . We speculate that these Smad‐independent pathways might be enhanced under ischemic conditions affecting CTGF expression in vivo.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge, the effect of an adenoviral Smad3 vector on CTGF protein levels in vivo has not yet been reported in the context of wound healing. Moreover, there is increasing evidence that CTGF is regulated to a significant extent by other intermediates, such as the transcriptional factors c‐Maf and Lc‐Maf independent of the canonical Smad‐dependent TGF‐β pathway 32 . We speculate that these Smad‐independent pathways might be enhanced under ischemic conditions affecting CTGF expression in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, there is increasing evidence that CTGF is regulated to a significant extent by other intermediates, such as the transcriptional factors c-Maf and Lc-Maf independent of the canonical Smad-dependent TGF-b pathway. 32 We speculate that these Smad-independent pathways might be enhanced under ischemic conditions affecting CTGF expression in vivo. The profibrotic role of CTGF is more relevant in scarring than in wound healing and CTGF levels tend to increase after POD 15.…”
Section: Discussionmentioning
confidence: 88%
“…Because the Lc-Maf protein is translated from a splice variant of c-Maf , both the c-Maf and Lc-Maf proteins were absent in these null mice [17]. Analysis of tibiae at various stages of embryonic and post-natal development showed that at E15.5, the number of hypertrophic chondrocytes was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Lc-Maf was shown to synergize with SOX9 to increase the expression of the cartilage-specific Col2a1 gene in 10T1/2 cells and MC615 chondrocytes by binding within a Col2a1 enhancer element to the short, 7-bp recognition element GGCTCTG [7]. Lc-Maf is a splice variant of c-Maf, it has a different 3′UTR region and the protein has an additional 10 amino acids at the carboxyl terminus [7, 17]. Using a probe from the 3′UTR of Lc-Maf, northern hybridizations revealed RNA expression in various mouse tissues, including cartilage [7, 17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation